The Strip SiPM: a study of single photon time resolution. (17th June 2021) - Doroud, K.; Kim, D.W.; Kwon, K.H.; Liu, Z.; Min, B.G.; Williams, M.C.S.; Zichichi, A.
Abstract: The Strip Silicon PhotoMultiplier (SiPM) allows a photosensitive area to be created that has excellent time resolution coupled to good position resolution. However, as the SiPM is made larger it becomes more difficult to extract the signal produced by a single photon; we thus are using the NINO ASIC as the front-end amplifier. The NINO ASIC dissipates 40 mW of heat per channel. SiPMs are sensitive to temperature; increasing the temperature leads to higher noise and a higher breakdown voltage. For the best timing performance the front-end electronics should be mounted as close to the SiPM as possible; however if, for example, the front-end electronics are mounted on the backside of the SiPM, it would be very difficult to control the temperature of the SiPM. Given this, we chose to mount the NINO ASIC on the printed circuit board (PCB) away from the strip SiPM so that a cooling system can be added. We present here the performance of an array of 16 strip SiPMs readout by 4 NINO ASICs coupled by ∼5 cm of PCB track length. The performance has been evaluated by the measurement of the Single Photon Time Resolution (SPTR) and also the position resolution along the strip determined from the time difference of the signals at each end.